THE MECHANICAL AND PHYSICAL PROPERTIES OF LEATHER TANNED BY VEGETABLE TANNIN: A META-ANALYSIS STUDY (Jurnal Teknologi Industri Pertanian, 2026)
Vegetable tanning is a promising technique to cut down on or get rid of chromium in traditional leather processing. It has already been used with a wide range of plant-based tannins. Even with this advancement, there aren't many systematic comparisons of how different vegetable tannins affect the quality of leather. This study performed a meta-analysis to assess the impact of vegetable tanning on essential physical and mechanical qualities of leather, utilizing data from thirteen peer-reviewed publications to fill this gap. Hedges' d was used to figure the effect sizes, and a random-effects model was used to put together results from several trials. Funnel plots were utilized to investigate potential publication bias. The meta-analysis showed that there were no big changes in shrinkage temperature, tensile strength, rip strength, or elongation at break (p > 0.05). However, certain plant sources were identified as significant contributors to the physical and mechanical properties of the resultant leather. On the other hand, the type of skin or the animal species did not have a big effect on the qualities of the leather. In general, the results reveal that the exact combination of tannins in the plant materials used for vegetable tanning has the largest effect on how leather works.Keywords: meta-analysis, sustainability, tanning, vegetable tannin